Randomized trial to assess the efficacy of combined Stichopus horrens and Channa striatus based cleanser and moisturizer compared to Cetrimide Lotion 1% and Petrolatum in treatment of stasis eczema / Noor Shazana Mustaffa - Mustaffa, Noor Shazana (2021)
Background : Stichopus horrens (sea cucumber) and Channa striatus (haruan fish) have been shown to effectively expedite wound healing process[1-6] and to treat multiple inflammatory disease. We aimed to assess the combination benefits of Stichopus horrens (SH) and Channa striatus (CS) in the treatment of chronic inflammatory skin disease like stasis eczema. Methods: This was a single center, randomized prospective, parallel, double-blinded comparative trial in patient with stasis eczema. Subjects were randomized 1:1 to receive either Treatment A (Stichopus horrens and Channa Striatus based cleanser and moisturizer) or Treatment B (Cetrimide lotion 1% and Petrolatum) which are to be used 3 times a day for 2 weeks. Clinical assessment was done using DASI score and DLQI which was assessed at week 0,1 and 2. Results: A total of 116 subjects were screened successfully and underwent this trial. From this trial, we found that Treatment A (Stichopus horrens and Channa Striatus based cleanser and moisturizer) has significant effect on improving sign of skin inflammation in stasis eczema (mean reduction for DASI Total W2 – W0: - 2.19 vs – 1.14, p-value < 0.001) and improves the patient quality of life (mean reduction DLQI W2 – W0 : - 1.00 vs – 0.62, p-value < 0.001) as compared to Treatment B (Cetrimide lotion 1% and Petrolatum). There is no adverse effect observed in both treatment arm Conclusions: Stichopus horrens and Channa striatus based cleanser and moisturizer can be used as an adjunct therapy in the treatment of stasis eczema.